Authorising a tradition: Theory, criticism and (self-)canonisation in French Caribbean writing. (February 2013) - McCusker, Maeve
As many critics have noted, Antillean literature has developed in tandem with a strong (self-)critical and theoretical body of work. The various attempts to theorise Antillean identity since the 1930s ( négritude, antillanité, créolité, relation ) have hugely enriched the literary scene and have put Antillean writing firmly on the world map. They have also undoubtedly contributed to a field that can be characterised as explosive, incestuous and highly self-referential. This article begins by examining the kinds of writing privileged in the postcolonial canon, both francophone and anglophone, and argues that the French-language field continues to favour writers who are associated with theoretical or speculative writing (Césaire, Glissant, Chamoiseau). From this perspective Maryse Condé appears to offer a particularly interesting counter-example. Undoubtedly a canonical Antillean writer, she is openly dismissive of theory, claiming to operate outside its boundaries. Yet she too is heavily involved in the work of criticism and in shaping readers' responses, as well as her own self-image, through criticism and theory. I argue that Condé, like Chamoiseau (who is often viewed as the more 'theoretical' writer), tends to supply the tools for analysis of her own writing through a strong awareness of, and ongoing contribution to, the critical field in which her work is read. Both authors thus work to consolidate their own, and often in turn each other's, position as canonical authors.